Balance Sheet Repair and Corporate Investment in Japan - Kang, Joong (Washington, D.C. : International Monetary Fund, 2014)
We trace Japanese firms' behavior over the last decades using aggregate corporate balance sheet data. Financial health of Japanese corporate sector has improved and firms paid back significant amount of debt and rebuilt their liquidity buffers. They also expanded abroad while the pace of corporate investment moderated. Regarding the latter, model estimates on aggregate corporate investment over the post bubble period show that expectation about future profitability, in particular medium-term demand outlook, has been the major driver, implying that a successful implementation of structural reforms could have positive impact even in the near term by improving the medium-term demand outlook.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet